NILAI PENDIDIKAN DALAM TEKS SILAKRAMANING AGURON-GURON - I Gede Agus Mahendra Adiguna; I Made Wirahadi Kusuma; I Nengah Arimbawa (Guna Widya: Jurnal Pendidikan Hindu, 2024)
Many of the phenomena that occur in the world of education related to the behavior of students in this global era tend to experience a decline in the morality and education of the character of Hinduism which is shown by starting to decrease the attitude of honesty, hard work, devotion to teachers, parents and their neighbors and the many values that deviate from education. The text is more accurate on the guidelines that must be applied by teachers and also students when seeking spiritual science. The teacher in this text is a figure who gives guidance to the teacher in order to the ultimate goal of moksha. In this regard, there is an ethics that must be held firm by the teacher and applied in everyday life to eternal liberation of sukha tan pawali dukha. This research belongs to qualitative research with descriptive analysis with an experimental approach so that the researchers are the key instruments. Data collection techniques are carried out in triangulation, data analysis is inductive and the results of quality research emphasize meaning rather than generalization. The primary source of data is from the literary text of Silakramaning Aguron-guron, the other books of his advocacy as well as field observations. From the results of data analysis it can be found that this study teaches or gives knowledge to a student to have good ethics to all living beings as well as assuming that the teacher is the parent at school.